98.1k views
2 votes
What is the explicit formula for the geometric sequence with this recursive formula?

What is the explicit formula for the geometric sequence with this recursive formula-example-1
What is the explicit formula for the geometric sequence with this recursive formula-example-1
What is the explicit formula for the geometric sequence with this recursive formula-example-2

2 Answers

2 votes

Answer:

A

Explanation:

a₁ = -3 ------> first term

r ----> common ratio


a_(n)=a_(n-1)*(1)/(8)\\\\r=(1)/(8)\\\\a_(n)=a_(1)*r^(n-1)\\\\a_(n)=-3*((1)/(8))^(n-1)

User Ratsstack
by
4.6k points
2 votes

Answer:

A an = -3 * (1/8) ^ (n-1)

Explanation:

We know the first term a1 = -3

And the common ratio r = 1/8 from the an = an-1 * 1/8

The explicit formula is

an = a1 r^ (n-1)

an = -3 * (1/8) ^ (n-1)

User Martin Gross
by
4.5k points